A geographical survey of Africa ; its rivers, lakes, mountains, productions, states, populations, &c. With a map of an entirely new construction, to which is prefixed a letter to Lord John Russell regarding the slave trade and the improvement of Africa /: its rivers, lakes, mountains, productions, states, populations, &c. With a map of an entirely new construction, to which is prefixed a letter to Lord John Russell regarding the slave trade and the improvement of Africa. (2014) - MacQueen, James, 1778-1870
No abstract available